The enhancement of sensitivity and response times of PDMS-based capacitive force sensor by means of active layer modification - Yasumin Siangkhio; Adirek Rangkasikorn; Narin Tammarugwattana; Navaphun Kayunkid; Sukittiya Jessadaluk; Sakon Rahong; Supamas Wirunchit; Jiti Nukeaw (Japanese Journal of Applied Physics, 2021)
Abstract In this work, sensitivity and response times of PDMS-based capacitive force sensors are enhanced via the modifications of the PDMS layer. Two modifying approaches are proposed; (i) change PDMS’s (elastomer:curing agent) ratio and (ii) adding conductive polymer PEDOT:PSS into the PDMS layer. The change of PDMS (elastomer:curing agent) ratio from (10:1) to (30:1) increases the sensitivity from 0.4 ± 0.08 to 0.72 ± 0.23 kPa −1 (+80%) but it does not significantly affect the response/recovery times. In addition, by adding 1% wt. of PEDOT:PSS to PDMS (30:1), the further increment of sensitivity from 0.72 ± 0.23 to 1.44 ± 0.17 kPa −1 (+100%) and the shorter response time from 1.59 ± 0.02 to 0.45 ± 0.03 s (−72%) are observed. The mechanical and electrical studies reveal that the change of PDMS (elastomer:curing agent) ratio and the adding of PEDOT:PSS to PDMS layer result in the modification of PDMS’s deformability and the increase of charge transportation, leading to the enhancement of sensing characteristics of the sensors.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Tactile and Sensory Interactions